Modulation of B-cell abnormalities in lupus-prone (NZB x NZW)F1 mice by normal bone marrow-derived B-lineage cells. - Shao, D Z (1995)
(NZB x NZW)F1(NZB/WF1) mice spontaneously develop an autoimmune disease characterized by abnormality of haemopoietic stem cells. The present study examined a possible regulatory cell interaction between NZB/WF1 and normal bone marrow cells using radiation-induced chimeras. We demonstrated that the ability of NZB/WF1 bone marrow cells to transfer the typical disease with hypergammaglobulinemia including autoantibodies into lethally irradiated normal recipients was prevented by cotransfer of bone marrow from normal CBA/J mice but not from xid CBA/N mice carrying a selective defect in B-cell function. Flow cytometric analysis revealed that the generation of NZB/WF1 cells was reduced in the mixed chimeras given CBA/J but not CBA/N bone marrow cells. Interestingly, radiation chimeras reconstituted with a mixture of NZB/WF1 bone marrow and CBA/J splenic B cells did not show elevation of serum immunoglobulin levels, although most of the spleen cells were dominated by NZB/WF1 cells. On the other hand, NZB/WF1 B cells maturated in vivo in the presence of CBA/J bone marrow or splenic B cells lost the hyper-responsiveness to lipopolysaccharide (LPS) in the autoantibody production in vitro. These results suggest that radiosensitive normal B-lineage cells have the regulatory activity to ameliorate the hypergammaglobulinemia of NZB/WF1 mice by reducing the generation of NZB/WF1 B cells and/or by correcting their hyper-responsiveness, and that NZB/WF1 mice may have a defect(s) in the regulatory cell function. In addition, CBA/J splenic B cells were shown to modulate the B-cell abnormality even when injected into non-irradiated NZB/WF1 mice manifesting autoimmunity.